2008
DOI: 10.1124/dmd.107.020180
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Saturable Intestinal Absorption of Metformin

Abstract: ABSTRACT:The purpose of the study was to elucidate mechanisms of metformin absorptive transport to explain the dose-dependent absorption observed in humans. Apical (AP) and basolateral (BL) uptake and efflux as well as AP to BL (absorptive) transport across Caco-2 cell monolayers were evaluated over a range of concentrations. Transport was concentration-dependent and consisted of saturable and nonsaturable components (K m ϳ 0.05 mM, J max ϳ 1.0 pmol min ؊1 cm ؊2, and K d, transport ϳ 10 nl min ؊1 cm ؊2 ). AP u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 29 publications
9
104
0
Order By: Relevance
“…Though bioavailability for most drugs is determined by absorption and metabolism in the gastrointestinal tract as well as hepatic metabolism, because metformin is not metabolized its bioavailability is determined primarily by intestinal absorption. These data, which suggest that metformin absorption is mediated by a saturable absorption process 9,14,33 , are consistent with a major role of intestinal influx transporters in the oral absorption of metformin.…”
Section: Transporters Involved In Metformin Intestinal Absorptionsupporting
confidence: 78%
“…Though bioavailability for most drugs is determined by absorption and metabolism in the gastrointestinal tract as well as hepatic metabolism, because metformin is not metabolized its bioavailability is determined primarily by intestinal absorption. These data, which suggest that metformin absorption is mediated by a saturable absorption process 9,14,33 , are consistent with a major role of intestinal influx transporters in the oral absorption of metformin.…”
Section: Transporters Involved In Metformin Intestinal Absorptionsupporting
confidence: 78%
“…The cells were passaged following 90% confluence using trypsin-EDTA, and plated at a 1:20 ratio in 75 cm 2 T-flasks. Caco-2 cells were cultured as described previously (Proctor et al, 2008). Briefly, the cells (passage numbers 30-40) were seeded at a density of 60,000 cells/cm 2 on polycarbonate membranes of Transwells (Corning Inc., Tewksbury, MA).…”
Section: Methodsmentioning
confidence: 99%
“…We have investigated the mechanism of intestinal absorption of metformin in the well established model of human intestinal epithelium, the Caco-2 cell monolayers (Proctor et al, 2008). The study showed that metformin was taken up efficiently across the apical (AP) membrane of Caco-2 cells by bidirectional cation-selective transporter(s) during absorptive transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that ER formulations can produce flip flop-like kinetics when the apparent k a <k el (k el /k a ratio >1) and could lead to miscalculations of the PK parameters (53). For pramipexole, we observed reductions in the C max BE space for values of k a ≤0.4 h −1 (k el /k a ratio=0.2).…”
Section: Discussionmentioning
confidence: 58%